The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/0104-9224/si2303.07
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação de Parâmetros de Soldagem nas Características de Juntas Dissimilares Inconel 718 - Inox 316L Soldadas pelo Processo TIG Autógeno

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution Non-Commercial, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que sem fins comerciais e que o trabalho original seja corretamente citado.Resumo: A aplicação de juntas soldadas dissimilares, de Inconel 718 endurecível por precipitação e aço inoxidável austenítico AISI316L, ocorre principalmente em indústrias aeroespaciais e plantas de usinas nucleares. Isso ocorre devido à ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
1
1
0
3
Order By: Relevance
“…The results of the dimensioning of the welded samples are shown in Figure 7. As observed by Royse [25] and Demarque et al [16], the weld bead dimensions increase with increasing heat input since higher heat inputs imply a higher amount of energy transferred to the metal, resulting in a greater weld pool, as shown in the graph results. It can be observed that the increase in the penetration of sample 3 (greater heat input) in relation to the penetration of sample 1 (lower heat input) was 6.2%, while the increase in the width of sample 3 in relation to the width of sample 1 was 49.6%, in other words, the increase in the width of the weld bead in relation to the heat input was more significant.…”
Section: Analysis Of Welded Samplessupporting
confidence: 65%
See 1 more Smart Citation
“…The results of the dimensioning of the welded samples are shown in Figure 7. As observed by Royse [25] and Demarque et al [16], the weld bead dimensions increase with increasing heat input since higher heat inputs imply a higher amount of energy transferred to the metal, resulting in a greater weld pool, as shown in the graph results. It can be observed that the increase in the penetration of sample 3 (greater heat input) in relation to the penetration of sample 1 (lower heat input) was 6.2%, while the increase in the width of sample 3 in relation to the width of sample 1 was 49.6%, in other words, the increase in the width of the weld bead in relation to the heat input was more significant.…”
Section: Analysis Of Welded Samplessupporting
confidence: 65%
“…Fixed inter-pass temperature and varied current were used, as shown in Table 4, where the welding parameters are found. The inter-pass temperature and current values were established in a previous study [16], in which an experimental planning was realized following the Calegare method [17]. Knowing that the η efficiency is equal to 0.8 for the autogenous GTAW process [18], the welding heat input was calculated according to Equation 1, whose results are also shown in Table 4.…”
Section: Welding Processmentioning
confidence: 99%
“…A Figura 5 mostra a microestrutura dos aços AISI 316 e AISI 316L, respectivamente. Observa-se a presença de grãos poligonais austeníticos, como observado em estudos anteriores por Tavares et al [14] e Demarque et al [15], além da presença de maclas de recozimento, que se formaram devido ao processo de laminação a quente das amostras CR.…”
Section: Análise Das Amostras Como Recebidasunclassified
“…Foram encontrados na literatura alguns trabalhos sobre a soldagem entre os aços Inconel e os inoxidáveis [4][5][6][7][8], no entanto não há estudos de resistência à corrosão através de ensaios de polarização cíclica combinando a junção especificamente do Inconel 718 com o aço 316L de forma autógena pelo processo TIG. Alguns estudos foram feitos com a mesma união e processo ou com união e processos similares, mas nenhum destes autores fizeram a utilização do levantamento dessas curvas para caracterizar a resistência à corrosão nesta junção.…”
Section: Introductionunclassified
“…Cortés et al [7] realizaram ensaios mecânicos como testes de impacto e dureza em chapas de Inconel 718 soldadas pelo processo TIG com a utilização de metal de adição e submetidas a recozimento após a soldagem. Demarque et al [8] realizaram estudos em amostras com a mesma composição avaliando a microestrutura obtida e utilizando modelamento estatístico para estimar as características metalúrgicas da zona fundida produzida por um processo autógeno. Rankumar [9,10] fez estudos em junções dos mesmos metais base de nosso estudo, porém utilizando processos distintos e ainda metais de adição, visando obter as propriedades metalúrgicas, mecânicas e de corrosão da união.…”
Section: Introductionunclassified